Teachers' perceptions on their principals' transformational leadership behaviors in the Sarikei division,Sarawak, Malaysia - Sali, Anak Sumoh (1998)
The primary purpose of this study was to assess the extent to which the secondary school principals in Sarikei Division, Sarawak were engaged in the transformational leadership behaviors. The teachersʼ perceptions on their principalsʼ transformational leadership behaviors (symbols/model behaviors dimension, collaborative structure dimension, individualized support dimension, intellectual stimulation dimension, performance expectations dimension, and vision and goals dimension) were utilized as independent variable while the school principals which were categorized according to school grades (grade A schools and grade B schools), school status (government secondary schools and government-aided secondary schools), and school types (boarding secondary schools and non-boarding secondary schools) were the dependent variables.